2023
DOI: 10.1200/jco.23.00187
|View full text |Cite
|
Sign up to set email alerts
|

Reply to W.H. Tong et al

Abstract: We thank Tong and Mertens 1 for their comments about the statistical methods used to analyze the ELIANA trial. The authors comment on the estimation method for relapse-free survival (RFS) and suggest an alternative approach. Before discussing different estimation methods, it is important to clarify the scientific questions of interest and what the target of estimation (estimand) is.genlecleucel and possible subsequent SCT on RFS analyzed by not censoring for SCT. NE, not estimable; RFS, relapse-free survival; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Our results strongly suggest that H. timareta acquired a regucalcin1 allele by hybridizing with its closely related comimic H. melpomene, increasing attraction toward red females and presumably reproductive success. By contrast, where H. melpomene co-occurs with the equally closely related but differently colored H. cydno, regucalcin1 contributes an important barrier to interspecific gene flow through its contribution to divergent mating preferences (11,38). As such, the evolutionary impact of regucalcin1 depends on the local mimetic landscape, emphasizing the complex role that hybridization may have on population divergence by reassembling genetic variants (39).…”
Section: Discussionmentioning
confidence: 99%
“…Our results strongly suggest that H. timareta acquired a regucalcin1 allele by hybridizing with its closely related comimic H. melpomene, increasing attraction toward red females and presumably reproductive success. By contrast, where H. melpomene co-occurs with the equally closely related but differently colored H. cydno, regucalcin1 contributes an important barrier to interspecific gene flow through its contribution to divergent mating preferences (11,38). As such, the evolutionary impact of regucalcin1 depends on the local mimetic landscape, emphasizing the complex role that hybridization may have on population divergence by reassembling genetic variants (39).…”
Section: Discussionmentioning
confidence: 99%
“…Although they serve as a foundation for testing the hypothesis of strict allopatry between two lineages, they are not sufficient on their own to provide a quantification of the timing of gene flow and thus to estimate the current status of reproductive isolation of a pair of taxa. Recent computational methods have allowed the explicit evaluation of alternative evolutionary scenarios, notably to test the occurrence of ongoing gene flow, as well as to test the semi-permeability of species barriers in the genomes (10,11). Applied to 61 pairs of animal taxa, these methods revealed that introgression is frequent until 2% of net divergences (6), and can even take place between lineages 14 times more divergent than the human-chimpanzee divergence (12).…”
Section: Introductionmentioning
confidence: 99%